2001
DOI: 10.1902/annals.2001.6.1.91
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Periodontal Diseases and Diabetes: An Overview

Abstract: Diabetes mellitus, caused by the malfunction of insulin-dependent glucose and lipid metabolism, presents with the classical triad of symptoms: polydypsia, polyuria, and polyphagia which are often accompanied by chronic fatigue and loss of weight. Complications of diabetes mellitus include retinopathy, nephropathy, neuropathy, and cardiovascular disease. Periodontal diseases are infections affecting the periodontium and resulting in the loss of tooth support. The association between diabetes mellitus and period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
212
0
19

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(251 citation statements)
references
References 47 publications
8
212
0
19
Order By: Relevance
“…Studies have supported a two-way relation between diabetes and periodontal status [6][7][8][9] . Key public strategies such as primary prevention and early diagnosis require deep knowledge related to risk factors and to the etiopathogenesis of the disease or diseases under analysis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have supported a two-way relation between diabetes and periodontal status [6][7][8][9] . Key public strategies such as primary prevention and early diagnosis require deep knowledge related to risk factors and to the etiopathogenesis of the disease or diseases under analysis.…”
Section: Discussionmentioning
confidence: 97%
“…The association between periodontal diseases and diabetes has been studied over the last decades and, today, there is enough scientific evidence to support the existence of a twoway relationship between them [6][7][8][9] . Diabetes increases the risk of incidence and severity for periodontitis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that hyperglycemia and subsequent biochemical events were correlated with the development of their diseases, although the precise mechanism of them remains unclear (3,4). It has been generally accepted that bacterial infection-induced inflammatory periodontal disease, so-called periodontitis, is one of the diabetic complications (5). Poor metabolic control of diabetes mellitus has often been associated with the severity of periodontitis (6).…”
mentioning
confidence: 99%
“…Se trata de una endocrinopatía con una serie de complicaciones típicamente asociadas, entre las cuales cada vez más autores optan por incluir la alteración periodontal y hablan de la periodontitis como la sexta complicación típica de la diabetes mellitus, al observar la elevada proporción de veces en las que ambas patologías confluyen en el mismo paciente (19,20).…”
Section: B Relacionadas Con El Inadecuado Control De La Glucemiaunclassified